IMF Research Bulletin, March 2001. (IMF Research Bulletin; IMF Research Bulletin ;, 2001)
The IMF Research Bulletin, a quarterly publication, selectively summarizes research and analytical work done by various departments at the Fund and also provides a listing of research documents and other research-related activities at the Fund, including conferences and seminars. The bulletin is intended to serve as a summary guide to research done at the IMF on various topics, and provide a better perspective on the analytical underpinnings of the IMF's operational work.